A computationally efficient numerical model for a dynamic analysis of thin plates based on the combined finite–discrete element method. (15th October 2015) - Uzelac, Ivana; Smoljanović, Hrvoje; Peroš, Bernardin
Highlights: New finite–discrete numerical model for analysis of plate structures is developed. The model is based on three-noded triangular finite element. Model considers linear elastic material, finite displacement and finite rotations. High accuracy is shown in comparison to other numerical models. Abstract: This paper presents a new numerical model for a static and dynamic analysis of thin plate structures based on the combined finite–discrete element method (FDEM). The model uses three-noded triangular finite elements taking into account linear-elastic material behaviour, finite rotations, finite displacements and small strains. The model is implemented into the open source FDEM package 'Yfdem'. Performance of the new numerical model was demonstrated on simple benchmark tests by a comparison with known analytical and numerical results.